The Effect of a Novel Theanine Complex (JDS-MT-003) on Sleep in a Caffeine-Induced Insomnia Mouse Model - Komorowski, James; Ojalvo, Sara; Sylla, Sarah; Mamedova, Havakhanum; Orhan, Cemal; Tuzcu, Mehmet; Kilic, Ertugrul (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA